2022
DOI: 10.1155/2022/3009494
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Low Dose Apatinib plus Chemotherapy on Advanced Gastric Carcinoma

Abstract: Objective. To evaluate the efficacy of low dose apatinib plus chemotherapy on advanced gastric carcinoma. Methods. Eligible 50 patients with advanced gastric carcinoma admitted to the hospital from January 2019 to March 2020 were enrolled, and they were assigned into the control group ( n = 25 , chemotherapy) and observation group (apatinib plus chemotherapy). Changes of CEA, CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…We searched 1594 studies from 7 databases.Of these studies, 826 duplicate studies were excluded and two reviewers independently assessed the remaining 768 studies to determine their eligibility.Next, a total of 752 studies were excluded due to the following reasons: no control group (286); insu cient data (98); full text unavailable (143); quality assessment exclusion (139); combined PD-1/PD-L1 ( 89).Finally, a total of 13 studies were included [17-29] [17][18][19][20][21][22][23][24][25][26][27][28][29] .The detailed literature search process is shown in Fig. 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched 1594 studies from 7 databases.Of these studies, 826 duplicate studies were excluded and two reviewers independently assessed the remaining 768 studies to determine their eligibility.Next, a total of 752 studies were excluded due to the following reasons: no control group (286); insu cient data (98); full text unavailable (143); quality assessment exclusion (139); combined PD-1/PD-L1 ( 89).Finally, a total of 13 studies were included [17-29] [17][18][19][20][21][22][23][24][25][26][27][28][29] .The detailed literature search process is shown in Fig. 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The characteristics of the studies nally included in the meta-analysis are shown in (Table 1). The studies were published between 2018 and July 2023, and were all conducted in China.The primary endpoint of this study is ORR and R0 resection rate; the secondary endpoint is DCR; the safety endpoint is any grade of AEs.A total of 1217 patients with advanced GC were included in 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] , including 652 patients in the observation group and 565 patients in the control group.The pathological type was adenocarcinoma in 6 studies [17,19,21,25,26,28] , and 7 studies did not describe it [18, 20, 22-24, 27, 29] .Some are located at the gastroesophageal junction [17,25,26] , and the rest are located in the stomach.In the observation group, 9 studies [18,19,21,[24][25][26][27][28][29] used low-dose apatinib (≥ 500 mg qd), and 3 studies [20,22,23] used high-dose apatinib. 1 item [17] is unknown.There are 8 studies using RCT [17, 18, 20-22, 24, 28, 29] .There are 5 studies using retrospective research [19,23,[25][26][27]…”
Section: Basic Characteristics and Quality Evaluation Of Included Lit...mentioning
confidence: 99%
“…[5][6][7] Apatinib, a novel TKI and antiangiogenic agent, has shown encouraging efficacy in advanced gastric adenocarcinoma and unresectable HCC. [8,9] In recent years, conclusions regarding the efficacy and safety of apatinib and sorafenib as first-line treatment for advanced HCC in direct comparative studies are still controversial. [10,11] Therefore, this meta-analysis aims to evaluate the efficacy and safety of a new TKI (apatinib) versus a traditional TKI (sorafenib) in the first-line treatment of advanced HCC, including the efficacy and safety differences between these 2 TKIs when combined with TACE, to provide evidence for clinical rational drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the RAINBOW, ATTRACTION-02 and KEYNOTE-059 clinical trial, antiangiogenic ramucirumab combined with chemotherapy and immunotherapy were approved by the FDA for the secondline and third-line treatment of metastatic gastric cancer (Wilke et al, 2014;Kang et al, 2017;Fuchs et al, 2018), respectively. Some small-sample retrospective studies suggested that antiangiogenic small-molecule multi-targeted tyrosine kinase inhibitors (TKIs) combined with chemotherapy, immune checkpoint inhibitors (ICIs) plus anti-angiogenesis may be potentially effective combination therapy strategies (Gao et al, 2022;Li et al, 2022;Tang et al, 2022). The present study aimed to evaluate the clinical efficacy and safety of chemotherapy, antiangiogenic TKIs + chemotherapy and TKIs + ICIs as second-line or above therapy options for advanced or metastatic gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Some small-sample retrospective studies suggested that anti-angiogenic small-molecule multi-targeted tyrosine kinase inhibitors (TKIs) combined with chemotherapy, immune checkpoint inhibitors (ICIs) plus anti-angiogenesis may be potentially effective combination therapy strategies ( Gao et al, 2022 ; Li et al, 2022 ; Tang et al, 2022 ). The present study aimed to evaluate the clinical efficacy and safety of chemotherapy, anti-angiogenic TKIs + chemotherapy and TKIs + ICIs as second-line or above therapy options for advanced or metastatic gastric cancer.…”
Section: Introductionmentioning
confidence: 99%